Konstruksi Personal Branding pada Avatar Game: Studi Kasus pada Komunitas LUXES Ayodance Mobile Indonesia - Irvia Amananda; Yuli Candrasari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to understand how players of Ayodance Mobile Indonesia build personal branding through avatars in the virtual world. The research uses a qualitative descriptive method with data collected through interviews, observation, and documentation. The analysis reveals that personal branding of avatars is based on various functions and purposes among players, focusing on attractive visual appearance and gaming skills. Players have the freedom to customize their avatar identities without using their real identities. Instagram plays an important role in strengthening personal branding by sharing visual content of avatars. Additionally, the Luxes community acts as a support system in the process of forming virtual identities.